(untitled) (CAHIERS MAGELLANES-NS, 2024)
The study, "An Analytical Study on Interest in Organic Chemistry among High School Students of Lawngtlai Town in Mizoram," investigates the level of interest in Organic Chemistry among high school students in Lawngtlai town, employing a quantitative method and stratified random sampling technique. The study observed a 99.50% moderate interest level, with low interest shown by 0.50% and no high-level interest. It evaluated the impact of gender, type of school, familial factors, and teacher-related factors on students' interest in Organic Chemistry. Findings indicate the need for heightened awareness and emphasis on the subject, along with recommendations for innovative teaching methods, engaging activities, and family involvement to bolster students' interest in Organic Chemistry.